Peningkatan Kapasitas Guru dalam Penyusunan Media Ajar Digital melalui Pelatihan Canva - Sanitha, Onie Dian; Iashania, Yunida; Kristianti, Novera; Fransisco, Theo (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2025)
The development of digital technology requires teachers to be able to design interesting, interactive, and relevant teaching media with the characteristics of today's students. However, there are still many teachers at the elementary school level who have not optimally utilized digital platforms to support the learning process. This community service activity aims to improve the capacity of teachers in compiling digital teaching media through training in the use of the Canva application. The activity was carried out at SMP Negeri 5 Palangka Raya with participants from teachers from various elementary schools in the surrounding area. The implementation method used a participatory approach with workshop and hands-on practice strategies, which included an introduction to the Canva feature, practice making infographics, interactive presentation slides, and visual-based student worksheets (LKPD). The results of the activity showed that this training was able to significantly improve teachers' digital skills, as shown through the initial and final evaluations of the training and the quality of the teaching media products produced by the participants. In addition, teachers felt more confident and motivated to develop creative and interesting teaching materials. This activity is expected to be a replication model for improving teachers' digital competence, especially in the context of information technology-based learning